Comparative performances of exotic and indigenous fish species with commercial culture systems of Mymensingh district in Bangladesh - Salam, S; Rana, KMS; Salam, MA (Progressive Agriculture, 2019)
An experiment was conducted to assess the relative performances of indigenous and exotic fish species under commercial culture system at Muktagacha and Trishal upazila in Mymensingh district. Six exotic fish species namely Thai koi (Anabas testudineus), Thai pangus (Pangusius hypophthalmus), Silver carp (Hypophthalmichthys molitrix), Vietnam koi (Anabas testudineus), Big head carp (Aristichthys nobilis) and Tilapia (Oreochromis niloticus) and nine indigenous fish species namely Rui (Labeo rohita), Shing (Heteropneustes fossilis), Sar punti (Puntius sarana), Gulsha (Mystus bleekeri), Koi (Anabas testudineus), Mrigal (Cirrhinus cirrhosus), Kalibaush (Labeo calbasu), Catla (Catla catla) and Magur (Clarias batrachus) were selected in Muktagacha while exotic Big head carp and indigenous Gulsha, Koi and Magur were lacking for observation in Trishal upazila. Results revealed that the production of exotic Thai pangus was comparatively higher in Muktagacha (5810.81 kg/acre) than Trishal (4521.74 kg/acre) upazila. In contrast, silver carp and tilapia production were 3063.04 kg/acre and 1008.26 kg/acre in Trishal, respectively which were higher than Muktagacha. Average selling price of tilapia, Vietnam koi and silver carp was also comparatively higher in Muktagacha than Trishal upazila. Similar observation was also obtained in respect of indigenous fish species. On the other hand, average selling price of shing was found highest (BDT. 333.33 per kg) in Muktagacha than Trishal while other fish species were sold at similar price. Gross income was also significantly higher with the exotic fishes in Muktagacha accounted for BDT. 858,716/acre/cycle while the highest gross income obtained with the indigenous fishes was in Trishal upazila, valued BDT. 121,5987/acre/cycle. It can be concluded that, both indigenous and exotic fish farming has spread in the area because of easy to adopt culture system, availability of fry, feed, good profit and high demand in the market. Some limitations of the ongoing practices have been identified that need to be addressed properly by the concerned authority. Progressive Agriculture 29 (4): 371-379, 2018